Shortest Route Navigation Indoors Using Digital Maps - Asis, Muhammad Arfah; Mude, Muh Aliyazid; Astiani, Ririn; Kurnia Prihandani, St Nadya (Indonesian Journal of Data and Science, 2023)
Digital maps have revolutionized our ability to navigate to desired locations by providing the shortest routes, primarily in open spaces. However, this functionality is limited to outdoor environments. This study aims to extend this capability by enabling the determination of the shortest routes within indoor spaces. The research employs the Haversine method for distance measurement and integrates the Dijkstra algorithm for route determination. The findings demonstrate the feasibility of implementing the Haversine method and the Dijkstra algorithm for route determination within enclosed spaces. The research results show that searching for the shortest route indoors be done and the route can be displayed on a digital map. It was observed that the routing machine between route nodes did not perform optimally, prompting its replacement with a polyline.